Biocompatibility Study with Baby Hamster Kidney Cells on Acetobacter Xylinum Pellicle for Diabetic Foot Laceration - Adanti Wido Paramadini; Faizah Faizah (Sean Institute, 2023)
Diabetes mellitus, commonly known as diabetes, is a persistent metabolic condition marked by elevated blood glucose levels. This condition's global prevalence has been consistently increasing, becoming a major cause for concern in public health on an international scale. This disease can lead to various complications, including impaired wound healing. The purpose of this study is to determine the cytotoxicity level of hydrogel membranes made from Acetobacter xylinum and whether the used method is appropriate for producing proper wound healing material. The findings of the study, employing BHK Kidney cells and the MTT Assay technique, revealed that the dehydrated hydrogel membrane derived from bacterial cellulose and processed through oven drying exhibited a toxicity level of less than 50% across all samples. Additionally, the swelling test indicated a rise in water absorption when the membrane was combined with collagen material